Novel cyanine dye as competitive ligand for probing the drug–nucleic acid interactions - O. Zhytniakivska; U. Tarabara; A. Kurutos; A. Zabrudska; K. Vus; V. Trusova; G. Gorbenko; T. Deligeorgiev (Біофізичний вісник, 2020)
Background: During the past decades, increasing attention has been given to elucidating the molecular details of interactions between the pharmacological agents and nucleic acids since the drug–DNA complexation may lead to impairment of DNA replication, strand breaking and mutations. A variety of techniques have been developed to characterize the drug-nucleic acid binding, among which the fluorescence dye displacement assay is one of the most informative approaches. Recently, it was demonstrated that cyanine dyes can be successfully employed for the high throughput screening of the interactions between nucleic acids and drugs. To the best of our knowledge, so far, the potential application of cyanine dyes for the drug-displacement studies remains insufficiently evaluated.